Method for producing polyamide-based resin foam particles and method for producing polyamide-based resin foam molding
The method enhances moldability and heat resistance of polyamide resin foam particles by incorporating specific thioether and hindered amine compounds, resulting in high-quality molded bodies with improved fusion, shape recovery, and appearance.
Patent Information
- Application Number
- JP2023170730
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Polyamide-based resin foam particles face challenges in moldability, with a narrow range of moldable pressures that affect the quality of molded bodies in terms of fusion properties, shape recovery, and appearance.
A method for producing polyamide resin foam particles involves preparing polyamide resin particles with a thioether compound and/or a hindered amine compound, followed by foaming using a physical foaming agent, with specific ratios of these compounds to enhance heat resistance and moldability.
The method results in polyamide resin foam particles with improved heat resistance and moldability, allowing for the production of molded bodies with excellent fusion properties, shape recovery, and appearance across a wide range of molding pressures.
Smart Images

Figure 2025060174000001 
Figure 2025060174000002 
Figure 2025060174000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing expanded polyamide resin particles having a polyamide resin as a main component of a base resin, and a method for producing an expanded molded polyamide resin article. [Background technology]
[0002] Polyamide resins are known as resins that have high heat resistance and are also excellent in abrasion resistance, chemical resistance, etc. A foam molded product obtained by foaming this polyamide resin can be made lighter while maintaining excellent properties such as heat resistance, abrasion resistance, and chemical resistance, etc. Therefore, polyamide resin foam molded products are expected to be used in automobile parts and other applications.
[0003] In order to further improve the heat resistance of polyamide resin foamed molded bodies, the addition of heat-resistant agents such as copper iodide has been considered. For example, Patent Document 1 discloses a technique for incorporating a base metal element-containing compound into polyamide resin foamed beads, and according to Patent Document 1, this technique makes it possible to obtain polyamide resin foamed beads with excellent thermal stability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2020 / 196893 Summary of the Invention [Problem to be solved by the invention]
[0005] However, although the heat resistance of expanded polyamide resin beads containing a heat-resistant agent such as copper iodide is improved, there is still room for improvement in the moldability for obtaining expanded bead moldings. Specifically, the expanded polyamide resin beads have problems in that the expanded beads are fusible with each other, the shape recovery after molding is poor, and the molding pressure range for obtaining a molded product having excellent appearance is narrow.
[0006] The present invention has been made in view of the above background, and aims to provide a method for producing expanded polyamide-based resin beads having excellent heat resistance and moldability, and a method for producing an expanded polyamide-based resin molded article having excellent heat resistance using the expanded polyamide-based resin beads. [Means for solving the problem]
[0007] One aspect of the present invention resides in a method for producing expanded polyamide resin beads according to the following items [1] to [4]. [1] A method for producing expanded polyamide resin beads, comprising the steps of: A step of preparing polyamide-based resin particles containing a base resin mainly composed of a polyamide-based resin and a compound (a) consisting of a thioether-based compound (a1) and / or a hindered amine-based compound (a2) having a molecular weight of 500 or more; and a step of expanding the polyamide-based resin particles using a physical foaming agent to obtain expanded polyamide-based resin particles, A method for producing expanded polyamide resin particles, wherein the compound (a) is added in an amount of 0.05 parts by mass or more and 1.5 parts by mass or less based on 100 parts by mass of the base resin.
[0008] [2] The method for producing expanded polyamide resin particles according to [1], wherein the polyamide resin particles further contain a compound (b) consisting of a hindered phenol compound (b1) and / or an organic phosphorus compound (b2). [3] The method for producing expanded polyamide resin particles according to [1] or [2], wherein the compound (a) contains at least one compound selected from the group consisting of hindered amine compounds represented by the following formula (1) and having a molecular weight of 500 or more, hindered amine compounds represented by the following formula (2) and thioether compounds represented by the following formula (3):
[0009] [ka] (In the above formula (1), n represents 2 to 10 repeating units.)
[0010] [ka] (In the above formula (2), n represents 1 to 10 repeating units.)
[0011] [ka] (Note that in the formula (3), each R independently represents an alkyl group having 1 to 20 carbon atoms.)
[0012] [4] The method for producing expanded polyamide resin particles according to any one of [1] to [3], wherein the amount of the compound (a) added is 0.3 parts by mass or more and 1 part by mass or less per 100 parts by mass of the base resin.
[0013] Another aspect of the present invention resides in a method for producing a polyamide resin foam molded article according to the following [5]. [5] A method for producing a polyamide-based resin foamed molded article, comprising molding the polyamide-based resin foamed beads produced by the above-mentioned production method in a mold. Effect of the Invention
[0014] According to the method for producing expanded beads, it is possible to provide a method for producing expanded polyamide resin beads having excellent heat resistance and moldability. Also, according to the method for producing a molded article, it is possible to produce a polyamide resin expanded molded article having excellent heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In this specification, "polyamide-based resin particles" may be referred to as "resin particles," "polyamide-based resin expanded particles" may be referred to as "expanded particles," and "polyamide-based resin expanded molded body" may be referred to as "molded body." In addition, when the symbol "~" is used to express a numerical range, it is used in a sense including the numerical values written before and after it.
[0016] [Method of manufacturing foam beads] The expanded beads are manufactured by the following preparation step and expansion step, and are used, for example, in the manufacture of a molded body. In the preparation step, polyamide-based resin particles containing a base resin mainly composed of a polyamide-based resin and a compound (a) are prepared. Specifically, for example, a base resin mainly composed of a polyamide-based resin and the compound (a) are melt-kneaded to obtain a polyamide-based resin melt, and the polyamide-based resin melt is granulated to obtain polyamide-based resin particles. In the preparation step, all operations can be performed in one step, but as described later, the preparation step can also be divided into, for example, a melt-kneading step in which a base resin mainly composed of a polyamide-based resin and the compound (a) are melt-kneaded, and a granulation step in which the polyamide-based resin melt is granulated to obtain polyamide-based resin particles. In the expansion step, polyamide-based resin particles are obtained by expanding the polyamide-based resin particles using a physical foaming agent. Each step will be described in detail below.
[0017] <Melting and kneading process> Base resin In the melt-kneading step, a base resin containing a polyamide resin as a main component is used. The main component is, for example, a component that exceeds 50 mass% of the resin components constituting the base resin. The content of the polyamide resin in the base resin is preferably 70 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more. It is particularly preferable that the base resin is substantially composed of only polyamide resin.
[0018] As the polyamide-based resin, for example, polyamide and polyamide copolymer are used. Polyamides include, for example, poly(6-aminohexanoic acid), also known as poly(caprolactam) (also known as polycaproamide, nylon 6), poly(laurolactam) (also known as nylon 12), poly(hexamethylene adipamide) (also known as nylon 66), poly(7-aminoheptanoic acid) (also known as nylon 7), poly(8-aminooctanoic acid) (also known as nylon 8), poly(9-aminononanoic acid) (also known as nylon 9), poly(10-aminodecanoic acid) (also known as nylon 10), poly(11-aminoundecanoic acid) (also known as nylon 11), and poly(12-aminobutanoic acid) (also known as nylon 12). Examples of such homopolymers include poly(hexamethylene sebacamide) (also known as nylon 11), poly(hexamethylene sebacamide) (also known as nylon 610), poly(decamethylene sebacamide) (also known as nylon 1010), poly(hexamethylene azelamide) (also known as nylon 69), poly(tetramethylene adipamide) (also known as nylon 46), poly(tetramethylene sebacamide) (also known as nylon 410), poly(pentamethylene adipamide) (also known as nylon 56), and poly(pentamethylene sebacamide) (also known as nylon 510). A polyamide copolymer refers to a copolymer having two or more types of repeating units, with at least a portion of each repeating unit having an amide bond. Examples of polyamide copolymers include polycaproamide / polyhexamethylene adipamide copolymer (also known as nylon 6 / 66), caprolactam / hexamethylenediaminoadipic acid / lauryl lactam (also known as nylon 6 / 66 / 12) copolymer, and caprolactam / lauryl lactam copolymer (also known as nylon 6 / 12). The polyamide resin may be one of these polyamides and polyamide copolymers, or two or more of them may be used in combination. Among the above polyamide resins, at least one selected from the group consisting of nylon 6, nylon 66, nylon 6 / 66, and nylon 6 / 66 / 12 is preferred, and nylon 6 / 66 and / or nylon 6 / 66 / 12 is more preferred.
[0019] The polyamide copolymer may be a block copolymer in which a certain amount of amides of the same repeating unit are followed by a certain amount of amides of different types, or a random copolymer in which different types of amides are randomly repeated, but is preferably a random copolymer. If the polyamide copolymer is a random copolymer, it becomes possible to mold the expanded beads at a lower molding pressure when molding them in a mold.
[0020] The polyamide resin may be a terminal-blocked polyamide resin in which the functional groups at the molecular chain ends are blocked. This makes it possible to more reliably suppress hydrolysis during the manufacturing process of the expanded beads, and makes it easier to obtain expanded beads that can withstand molding in a mold. Furthermore, the durability of the molded product is improved.
[0021] A terminal blocking agent can be used to block the molecular chain ends. Examples of terminal blocking agents include carbodiimide compounds, oxazoline compounds, isocyanate compounds, and epoxy compounds, among which carbodiimide compounds are preferred. Specific examples include aromatic monocarbodiimides such as bis(dipropylphenyl)carbodiimide (e.g., "Stabaxol 1-LF" manufactured by Rhein Chemie), aromatic polycarbodiimides (e.g., "Stabaxol P", "Stabaxol P100", "Stabaxol P400" manufactured by Rhein Chemie), and aliphatic polycarbodiimides such as poly(4,4'-dicyclohexylmethanecarbodiimide) (e.g., "Carbodilite LA-1" manufactured by Nisshinbo Chemical Co., Ltd.). These terminal blocking agents may be used alone or in combination of two or more.
[0022] The amount of the end blocking agent is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 3 parts by mass, based on 100 parts by mass of the polyamide resin.
[0023] Other thermoplastics In the melt-kneading step, other thermoplastic resins can be added as the base resin in addition to the polyamide resin, within the range that does not impair the intended effect of the present invention. Examples of other thermoplastic resins include polyethylene resins, polypropylene resins, polystyrene resins, vinyl acetate resins, thermoplastic polyester resins, acrylic acid ester resins, methacrylic acid ester resins, modified polyphenylene ether resins, polycarbonate resins, polyacetal resins, polybutylene terephthalate resins, polysulfone resins, polyethersulfone resins, polyamideimide resins, polyetherimide resins, polyetheretherketone resins, polyarylene sulfide resins, etc.
[0024] ·Compound (a) As the compound (a), a thioether-based compound (a1) and / or a hindered amine-based compound (a2) is used. The molecular weight of the hindered amine-based compound is 500 or more. The expanded beads and molded articles obtained by the manufacturing method of the present disclosure contain a compound composed of a polyamide-based resin and a hindered amine-based compound and / or a thioether-based compound, so that the shrinkage rate of the molded article after exposure to a high-temperature environment can be reduced and the molded article has excellent heat resistance. The compound (a) can exhibit a function as a heat resistance agent, and the expanded beads obtained by the manufacturing method of the present disclosure have excellent moldability, so that the expanded beads can be produced in a wide moldable range, with excellent shape recovery after molding, and excellent fusion between the expanded beads and excellent appearance. In addition, the expanded beads obtained by the manufacturing method of the present disclosure can be expanded at a higher expansion ratio than expanded beads manufactured under the same manufacturing conditions except that the hindered amine compound and the thioether compound are not used, so that the density of the expanded beads and the molded body can be reduced, and weight reduction can be facilitated. Furthermore, even if the molded body is exposed to a high-temperature environment, discoloration such as yellowing does not progress easily, and shrinkage does not easily occur.
[0025] In general, polyamide resin foam molded articles are susceptible to shrinkage over time in a high-temperature environment, and tend to shrink significantly after exposure to a high-temperature environment; however, by using a thioether compound and / or a hindered amine compound having a molecular weight of 500 or more as disclosed herein, it is possible to reduce the shrinkage of the molded article after exposure to a high-temperature environment.
[0026] If the molecular weight of the hindered amine compound is less than 500, the molded article may be more likely to shrink in a high-temperature environment. From the viewpoint of further preventing shrinkage in a high-temperature environment, the molecular weight of the hindered amine compound is preferably 1000 or more, more preferably 1500 or more. The upper limit of the molecular weight of the hindered amine compound is about 10,000.
[0027] As the hindered amine compound having a molecular weight of 500 or more, it is preferable to use a compound having an NH-type hindered amine structure, and it is more preferable to use a compound having at least one triazine structure and a 2,2,6,6-tetramethylpiperidine structure. It is also preferable to use a compound having at least one cyclic amine structure of a six-membered ring. Specifically, poly[6-(1,1,3,3-tetramethylbutyl)imino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidyl)imino](, a polycondensate of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine, etc. can be used.
[0028] The thioether compound may be a compound having an ester structure, such as tetrakis[3-(dodecylthio)propionic acid]methanetetrayltetrakismethylene, or ditridecyl 3,3-thiobispropionate.
[0029] From the viewpoint of further improving the heat resistance of the molded article, the molecular weight of the thioether-based compound is preferably at least 600, and more preferably at least 1000. The molecular weight means the weight average molecular weight.
[0030] The compound (a) preferably contains at least one compound selected from the group consisting of a hindered amine compound having a molecular weight of 500 or more and represented by the following formula (1), a hindered amine compound having a molecular weight of 500 or more and represented by the following formula (2), and a thioether compound having a molecular weight of 500 or more and represented by the following formula (3). In this case, expanded beads having excellent moldability and heat resistance are obtained, and the heat resistance of the molded body is further improved. From the above viewpoint, the content of the thioether compound represented by the following formula (3) in the thioether compound (a1) is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. From the above viewpoint, the content of the hindered amine compound represented by the following formula (1) and the hindered amine compound represented by the following formula (2) in the hindered amine compound (a2) is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0031] [ka]
[0032] [ka]
[0033] [ka]
[0034] In formula (1), n is 2 to 10. From the viewpoint of further improving heat resistance by adjusting the molecular weight appropriately, in formula (1), n is preferably 3 to 8, more preferably 4 to 6. The molecular weight of formula (1) is preferably 1500 to 4000, more preferably 2000 to 3100. A specific example of the hindered amine compound represented by formula (1) is poly[6-(1,1,3,3-tetramethylbutyl)imino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidyl)imino].
[0035] In formula (2), n is 1 to 10. From the viewpoint of further improving heat resistance by adjusting the molecular weight appropriately, n in formula (2) is preferably 2 to 8, and more preferably 2 to 6. The molecular weight of formula (2) is preferably 1500 to 5000, and more preferably 2600 to 3400. A specific example of the hindered amine compound represented by formula (2) is a polycondensate of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine.
[0036] In formula (3), R each independently represents an alkyl group having 1 to 20 carbon atoms. From the viewpoint of further improving heat resistance by adjusting the molecular weight appropriately, R in formula (3) is preferably an alkyl group having 3 to 16 carbon atoms, more preferably an alkyl group having 8 to 14 carbon atoms, and further preferably an alkyl group having 12 carbon atoms. A specific example of the thioether compound represented by formula (3) is tetrakis[3-(dodecylthio)propionic acid]methanetetrayltetrakismethylene. Tetrakis[3-(dodecylthio)propionic acid]methanetetrayltetrakismethylene has an alkyl group having 12 carbon atoms as R in formula (3).
[0037] The total amount of the thioether compound (a1) and the hindered amine compound (a2) having a molecular weight of 500 or more added relative to 100 parts by mass of the base resin is 0.05 parts by mass or more and 1 part by mass or less. If the total amount is less than 0.005 parts by mass, the effect of the addition is not sufficient, and the heat resistance of the expanded beads and the molded product may be insufficient. On the other hand, if the total amount is more than 1 part by mass, the closed cells of the expanded beads during molding in the mold may not be maintained, and the secondary foaming property may decrease, resulting in poor moldability. From the viewpoint of further improving the heat resistance and moldability by adding the thioether compound (a1) and the hindered amine compound (a2) having a molecular weight of 500 or more, the total amount of the thioether compound (a1) and the hindered amine compound (a2) having a molecular weight of 500 or more added relative to 100 parts by mass of the base resin is preferably 0.1 to 0.9 parts by mass, more preferably 0.2 to 0.8 parts by mass, and even more preferably 0.3 to 0.7 parts by mass.
[0038] In addition, to the extent that the intended object of the present invention is not impaired, other heat-resistant compounds other than the thioether-based compound (a1) and the hindered amine-based compound (a2) having a molecular weight of 500 or more may be added to the base resin. As the other heat-resistant compounds, organic compounds such as bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, copper halides such as copper iodide and copper bromide, and inorganic compounds such as copper acetate (I) can be used. The amount of the other heat-resistant compounds composed of organic compounds is preferably 0.1 parts by mass or less (including 0), more preferably 0.07 parts by mass or less (including 0), and even more preferably 0.05 parts by mass or less (including 0) relative to 100 parts by mass of the base resin.
[0039] In the step of obtaining a polyamide-based resin melt, it is preferable to further add a compound (b) consisting of a hindered phenol-based compound (b1) and / or an organic phosphorus-based compound (b2) and melt-knead the compound. In this case, the compound (b) capable of exerting an effect as an antioxidant provides an antioxidant effect on the polyamide-based resin, and the compound (a) and the compound (b) have a synergistic effect of further improving moldability and expanding ratio, thereby enabling further weight reduction of the expanded particles and molded bodies. This is considered to be because the compound (a) consisting of a thioether-based compound (a1) and / or a hindered amine-based compound (a2) having a molecular weight of 500 or more and the compound (b) consisting of a hindered phenol-based compound (b1) and / or an organic phosphorus-based compound (b2) are combined to suppress hydrolysis of the polyamide-based resin. From the viewpoint of further exerting this synergistic effect, it is preferable to add the compound (a) and the compound (b) at the same timing and melt-knead the compound. In addition, the compound (b) can exert a function as an antioxidant.
[0040] The hindered phenol compound preferably has 2 to 6 hindered phenol structures, more preferably has two hindered phenol structures. The hindered phenol compound preferably has an amide bond, more preferably a hindered hindered phenol compound having an amide bond. When the hindered amine compound is a hindered hindered phenol compound having an amide bond, the hindered amine compound preferably has 2 to 6 amide bonds and 2 to 6 hindered hindered phenol structures, more preferably has 2 to 6 di-tert-butyl-4 hydroxyphenyl alkyl carbonyl amide groups, and the number of carbon atoms in the alkyl chain portion in the di-tert-butyl-4 hydroxyphenyl alkyl carbonyl amide group is preferably 1 to 5, more preferably 2 to 4. The hindered phenol compound is particularly preferably N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4 hydroxyphenyl propionamide], which is a compound represented by the following formula (4).
[0041] [ka]
[0042] Examples of the organic phosphorus compound that can be used include phosphite triesters, such as tris(isodecyl)phosphite, tris(tridecyl)phosphite, phenyl isooctyl phosphite, phenyl isodecyl phosphite, phenyl di(tridecyl)phosphite, diphenyl isooctyl phosphite, diphenyl isodecyl phosphite, diphenyl tridecyl phosphite, triphenyl phosphite, tris(nonylphenyl)phosphite, 4,4'isopropylidenediphenol alkyl phosphite, trisnonylphenyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, tris(biphenyl)phosphite, distearyl pentaerythritol diphosphite, di(2,4-di-t-butylphenyl)phosphite, and the like. di(nonylphenyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, tetratridecyl 4,4'-butylidenebis(3-methyl-6-t-butylphenol) diphosphite, hexatridecyl 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane triphosphite, 3,5-di-t-butyl-4-hydroxybenzyl phosphite diethyl ester, sodium bis(4-t-butylphenyl)phosphite, sodium-2,2-methylene-bis(4,6-di-t-butylphenyl)-phosphite, 1,3-bis(diphenoxyphosphonyloxy)-benzene, ethyl bis(2,4-ditert-butyl-6-methylphenyl) phosphite, and the like. As the organic phosphorus compound, oligomer type and polymer type compounds having a phosphite structure can also be used. The organic phosphorus compound is preferably tris(2,4-di-t-butylphenyl)phosphite represented by the following formula (5).
[0043] [ka]
[0044] In the melt-kneading step, various additives such as bubble nucleating agents, antistatic agents, conductivity imparting agents, lubricants, ultraviolet absorbers, flame retardants, metal deactivators, crystal nucleating agents, colorants, and fillers can be appropriately added as necessary. The amount of these various additives added varies depending on the purpose of use of the molded body, but is preferably 25 parts by mass or less per 100 parts by mass of the base resin. More preferably, it is 15 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less.
[0045] In the melt-kneading step, carbon black can be added as a colorant. In this case, it is possible to produce expanded beads and molded articles that have a high degree of blackness and are less likely to discolor over time even in a high-temperature environment. Therefore, the expanded beads and molded articles are suitable for use as vehicle components (specifically, interior and exterior components). When carbon black is added, the amount of carbon black added is preferably 1 part by mass or more and 5 parts by mass or less, more preferably 2 parts by mass or more and 4 parts by mass or less, relative to 100 parts by mass of the base resin.
[0046] The melt-kneading is carried out, for example, in an extruder. The resin temperature during melt-kneading in the extruder is, for example, the melting point of the base resin + 40° C. to the melting point of the base resin + 80° C. The resin temperature is the resin temperature at the head portion at the tip of the extruder.
[0047] <Granulation process> In the granulation step, the polyamide-based resin melt is granulated. This produces polyamide-based resin particles. Granulation is carried out, for example, as follows. First, the polyamide-based resin melt is extruded in the form of a strand from an extruder, and the extruded strand is cooled and solidified. Next, the solidified strand is cut. In this manner, the polyamide-based resin melt is granulated, and resin particles can be obtained.
[0048] The melt flow rate (i.e., MFR) of the resin particles is preferably 1 to 5 g / 10 min. In this case, expanded beads having a low apparent density due to excellent expandability are easily obtained, and the heat resistance of the expanded bead molding is further improved. From the viewpoint of further improving this effect, the MFR of the resin particles is more preferably 1.5 to 4.5 g / 10 min, and further preferably 2 to 4 g / 10 min.
[0049] The MFR of the base resin is 1 g / 10 min or more and 8 g / 10 min or less, and the MFR of the base resin (i.e., F r ) and the MFR of the resin particles (i.e., F b ) (i.e., F r -F b ) is preferably 0 g / 10 min or more and 2 g / 10 min or less. In this case, the MFR of the resin particles is not higher than the MFR of the base resin, and the MFR of the resin particles is close to the MFR of the base resin, so that the expandability is improved, and expanded particles with a low apparent density are easily obtained, and moldability is further improved. From the viewpoint of further improving this effect, the MFR of the base resin is more preferably 1 g / 10 min or more and 7 g / 10 min or less, and even more preferably 2 g / 10 min or more and 5 g / 10 min or less. From the same viewpoint, the difference F r -F b It is more preferable that the MFR is 0 g / 10 min or more and 0.8 g / 10 min or less. A possible cause of the high MFR of the resin particles is hydrolysis of the base resin in the process of preparing the polyamide resin particles (for example, the melt-kneading process).
[0050] The MFR of the base resin, the MFR of the resin particles, and the MFR of the expanded particles are values measured based on JIS K7210-2:2014 under conditions of a test temperature of 230°C and a load of 2.16 kg. The test pieces used for measuring the MFR are dried at 80°C for 4 hours or more. The MFR of the base resin can be adjusted to a desired range, for example, by adjusting the composition of the base resin and the type of polyamide resin. The MFR of the resin particles can be adjusted to a desired range, for example, by adjusting the composition of the base resin, the type of polyamide resin, the type and blending ratio of compound (a), the type and blending ratio of compound (b), etc.
[0051] <Foaming process> In the foaming step, the resin particles are foamed using a physical foaming agent. Specifically, the resin particles are impregnated with the physical foaming agent, and the resin particles containing the foaming agent are foamed by heating, pressure change, volume change, etc., thereby obtaining foamed particles.
[0052] As the physical foaming agent, organic physical foaming agents and inorganic physical foaming agents can be used. Examples of organic physical foaming agents include aliphatic hydrocarbons such as propane, butane, pentane, hexane, and heptane; alicyclic hydrocarbons such as cyclopentane and cyclohexane; halogenated hydrocarbons such as chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride, and methylene chloride; and dialkyl ethers such as dimethyl ether, diethyl ether, and methyl ethyl ether. Examples of inorganic physical foaming agents include carbon dioxide, nitrogen, helium, argon, and air.
[0053] Among the physical blowing agents, from the viewpoints of having little impact on the environment, being non-flammable and having excellent safety, inorganic physical blowing agents are preferred, carbon dioxide or nitrogen are more preferred, and carbon dioxide is even more preferred.
[0054] The foaming step is not particularly limited as long as it involves impregnation of the resin particles with a foaming agent and foaming of the resin particles. For example, the foaming step is carried out by the following method [1] or [2]. [1] A method in which resin particles are impregnated with a foaming agent, the resin particles impregnated with the foaming agent are removed without being foamed, and then heated in a foaming device to obtain foamed particles. [2] A method of obtaining foamed particles by impregnating resin particles dispersed in a dispersion medium (specifically, a liquid) in a sealed device with a foaming agent, raising the temperature to near the softening point of the resin, and then releasing the resin particles together with the dispersion medium outside the device under low pressure. The foaming step is preferably carried out by the method [2] above.
[0055] The method [2] is explained in further detail below.
[0056] The foaming step is preferably carried out through the following steps: dispersing step, impregnation step, holding step, and releasing step. (1) In the dispersing step, resin particles are dispersed in water in a closed vessel to obtain a dispersion. (2) In the impregnation step, the resin particles in the dispersion are impregnated with a physical foaming agent. (3) In the holding step, the dispersion is held at a temperature that is 90° C. lower than the melting point (Tm) of the resin particles (Tm-90° C.) and lower than 50° C. lower (Tm-50° C.) for a holding time of 1 minute to 60 minutes. (4) In the release step, the temperature (Te) of the dispersion liquid immediately before foaming is set to a temperature that is 90°C lower than the melting point (Tm) of the resin particles (Tm - 90°C) or higher and lower than a temperature that is 50°C lower than the melting point (Tm) of the resin particles (Tm - 50°C), and the resin particles containing the foaming agent are released together with water from the sealed container under a pressure lower than the pressure inside the sealed container to cause foaming. The foaming step may include a step other than the dispersing step, the impregnation step, the holding step, and the releasing step, and other components may be added in any of the steps. The impregnation step and the holding step may be performed simultaneously, and the holding step may be performed before or after the impregnation step.
[0057] (Dispersion process) The dispersion step is a step of dispersing resin particles in water in a closed container to obtain a dispersion liquid. The method of dispersing resin particles in water is not particularly limited, and a known method can be used. For example, a dispersion liquid can be obtained by adding resin particles to water while stirring the water using a stirrer, and further stirring. In addition, it is preferable to add a dispersant such as an inorganic substance such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, mica, talc, smectite, etc.; or a dispersion assistant such as an anionic surfactant such as sodium dodecylbenzenesulfonate or sodium alkanesulfonate, etc., to the dispersion liquid as necessary. The mass ratio of the resin particles to the dispersant (resin particles / dispersant) is preferably 20 to 2000, more preferably 30 to 1000. In addition, the mass ratio of the dispersant to the dispersion assistant (dispersant / dispersant) is preferably 1 to 500, more preferably 1 to 100.
[0058] (Impregnation process) The impregnation step is a step of impregnating the resin particles in the dispersion with a foaming agent. The resin particles can also be made to absorb water at the same time. The method of impregnating the resin particles with the foaming agent is not particularly limited, but it is preferable to disperse the resin particles in water in a pressurizable closed container such as an autoclave and impregnate the resin particles with the foaming agent. In addition to pressurization, it is preferable to heat the resin particles when impregnating them with the foaming agent, in order to sufficiently impregnate the resin particles with the foaming agent in a short time.
[0059] The impregnation step includes a step in which the pressure in the sealed container reaches the pressure during impregnation (hereinafter also referred to as the impregnation pressure) from atmospheric pressure when pressurization is performed, and the step of impregnating with a foaming agent includes a step of heating a dispersion liquid in which resin particles are dispersed in water from room temperature to the temperature during impregnation (hereinafter also referred to as the impregnation temperature).
[0060] When the impregnation step is carried out under heating, from the viewpoint of sufficiently impregnating the resin particles with the foaming agent in a short time, the impregnation temperature is preferably 50°C or higher, more preferably 80°C or higher, and is preferably the melting point of the resin particles (Tm(°C)) or lower, more preferably (Tm-20(°C)) or lower.
[0061] In addition, from the viewpoint of impregnating the resin particles with the foaming agent sufficiently in a short time, the pressure during impregnation under pressure (hereinafter also referred to as the impregnation pressure) is set so that the pressure inside the sealed container is preferably 1.5 MPa (G) or more, more preferably 2.5 MPa (G) or more, preferably 7 MPa (G) or less, and more preferably 5 MPa (G) or less by adding the foaming agent to the container containing the dispersion. Note that "(G)" means gauge pressure, and for example, "1.5 MPa (G)" means that the gauge pressure is 1.5 MPa.
[0062] The dispersion step and the impregnation step also serve to allow the resin particles to absorb water. From the viewpoint of allowing the resin particles to sufficiently absorb water and plasticize, the total time of the step of obtaining a dispersion and the step of impregnating a blowing agent is preferably 20 minutes or more, more preferably 30 minutes or more. On the other hand, from the viewpoint of productivity of the expanded beads, the time is preferably 60 minutes or less. In addition, from the viewpoint of allowing the resin particles to sufficiently absorb water and plasticize, the temperature rise rate in the impregnation step is preferably 10° C. / min or less, more preferably 7° C. / min or less. On the other hand, from the viewpoint of productivity of the expanded beads, the temperature rise rate is preferably 1° C. / min or more, more preferably 2° C. / min or more.
[0063] (holding process) The holding step is a step of holding the dispersion at a temperature (Tm-90°C) 90°C lower than the melting point (Tm) of the resin particles and lower than a temperature (Tm-50°C) 50°C lower for a holding time of 1 minute to 60 minutes. The holding temperature of the dispersion in the holding step is 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher, preferably 80°C lower than the melting point (Tm-80°C) or higher, more preferably 70°C lower than the melting point (Tm-70°C) or higher, and even more preferably 65°C lower than the melting point (Tm-65°C) or higher, and is lower than 50°C lower than the melting point (Tm-50°C), preferably 55°C lower than the melting point (Tm-55°C), more preferably 57°C lower than the melting point (Tm-57°C), and even more preferably 59°C lower than the melting point (Tm-59°C).
[0064] Usually, when manufacturing expanded beads using a general-purpose resin such as a polypropylene resin as a base resin, the temperature is maintained near the melting point of the raw material resin. However, in a manufacturing method of expanded beads using a polyamide resin as the main component of the base resin, it is preferable to maintain the temperature at a temperature 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher and 50°C lower than the melting point (Tm) of the resin particles (Tm-50°C). This is because polyamide resins are hygroscopic, so the resin particles are plasticized by the water used as a dispersion liquid, and the melting point is significantly lowered, and as a result, it is possible to manufacture expanded beads at a temperature significantly lower than the melting point of the resin particles.
[0065] The holding time in the holding step is preferably 1 minute or more, more preferably 5 minutes or more, even more preferably 10 minutes or more, and even more preferably 13 minutes or more, from the viewpoint of uniformly impregnating the resin particles with the blowing agent and obtaining expanded particles having a high closed cell ratio. From the viewpoint of productivity of the expanded particles and the viewpoint of preventing hydrolysis of the polyamide resin, the holding time in the holding step is preferably 60 minutes or less, more preferably 40 minutes or less, even more preferably 30 minutes or less, even more preferably 20 minutes or less, and particularly preferably 18 minutes or less. By holding for the above time, it is possible to obtain expanded polyamide resin particles having a low apparent density and a high closed cell ratio. The holding step can be set in multiple stages within the above temperature range, and it is also possible to slowly increase the temperature within the temperature range over a sufficient period of time. From the viewpoint of easy production, it is preferable to set the temperature in one stage (the holding temperature is constant) within the above temperature range and hold for the above time.
[0066] The holding step is preferably carried out under pressure from the viewpoint of uniformly impregnating the resin particles with the foaming agent, and is preferably maintained at the same pressure as the impregnation pressure. The pressure in the vessel containing the dispersion is preferably 1.5 MPa (G) or more, more preferably 2.5 MPa (G) or more. The pressure in the vessel containing the dispersion is preferably 7 MPa (G) or less, more preferably 5 MPa (G) or less.
[0067] (Release process) The releasing step is a step of foaming the resin particles impregnated with the foaming agent, and is carried out by releasing the resin particles impregnated with the foaming agent together with water into a pressure atmosphere (usually atmospheric pressure) lower than the pressure in the holding step, and foaming is carried out. The releasing step is carried out, for example, following the holding step.
[0068] The temperature Te of the dispersion immediately before foaming (hereinafter also referred to as the foaming temperature) is preferably 90° C. lower than the melting point (Tm) of the resin particles (Tm-90° C.) or higher, more preferably 80° C. lower than the melting point (Tm-80° C.) or higher, even more preferably 70° C. lower than the melting point (Tm-70° C.) or higher, and even more preferably 65° C. lower than the melting point (Tm-65° C.) or higher, from the viewpoint of obtaining foamed particles having a low apparent density and a high closed cell ratio. In addition, the foaming temperature is preferably less than 50° C. lower than the melting point (Tm) of the resin particles (Tm-50° C.), more preferably 55° C. lower than the melting point (Tm) of the resin particles (Tm-55° C.), even more preferably 57° C. lower than the melting point (Tm-57° C.), and even more preferably 59° C. lower than the melting point (Tm-59° C.).
[0069] The pressure immediately before the release in the release step (foaming pressure) is preferably 0.5 MPa (G) or more, more preferably 1.5 MPa (G) or more, and even more preferably 2.5 MPa (G) or more. The foaming pressure is preferably 10 MPa (G) or less, more preferably 7 MPa (G) or less, and even more preferably 5 MPa (G) or less.
[0070] [Foam particles] (Apparent density) The apparent density of the foam particles is 50 to 200 kg / m 3 In this case, the expanded beads and the molded article have excellent light weight and can fully exhibit the mechanical properties of the polyamide resin. From the viewpoint of further improving this effect, the apparent density of the expanded beads is preferably 55 to 150 kg / m 3 More preferably, it is 60 to 130 kg / m 3 The apparent density is measured as follows. First, a sample of about 500 cm2 is left for 2 days under the conditions of 50% relative humidity, 23°C, and 1 atm. 3 The mass W1 of the foamed beads is measured. Next, a measuring cylinder containing water at a temperature of 23°C is prepared, and the foamed beads whose mass has been measured are submerged in the measuring cylinder using a wire net. Taking into account the volume of the wire net, the volume V1 of the foamed beads is read from the rise in the water level [unit: cm 3] is measured, and the mass W1 [g] of the foamed particles is divided by the volume V1 (W1 / V1), and the unit is [kg / m 3 The apparent density of the expanded beads is calculated by converting this to
[0071] (Percentage reduction in apparent density) The reduction ratio Ds / De of the apparent density De of the expanded beads containing the above-mentioned compound (a) and / or compound (b) to the apparent density Ds of the expanded beads not containing the compound (a) and compound (b) is preferably more than 1.0, more preferably 1.1 or more, and even more preferably 1.2 or more. In this case, the lightness of the expanded beads and the molded article is further improved. Note that Ds / De is generally 1.5 or less.
[0072] (MFR) The MFR of the expanded beads is preferably 0.5 g / 10 min or more and 5 g / 10 min or less. Even when the expansion ratio of the expanded beads is high, the expanded beads and the molded article can fully exhibit the excellent mechanical properties of the polyamide resin. From the viewpoint of further improving this effect, the MFR of the expanded beads is preferably 1 g / 10 min or more and 4 g / 10 min or less, and more preferably 1.5 g / 10 min or more and 3.5 g / 10 min or less. The MFR of the expanded beads is measured by the same method as the MFR of the resin particles described above. In addition, the MFR of the expanded beads can be adjusted to a desired range, for example, by the same method as the MFR of the resin particles.
[0073] [Method of manufacturing molded body] The expanded beads are molded in a mold to obtain a molded article, which is formed by fusing the expanded beads together.
[0074] The in-mold molding method can be a conventionally known method, but it is preferable to use heating with steam. The polyamide resin in the expanded beads absorbs water and plasticizes by steam, making it possible to reduce the molding pressure. If the obtained molded body is dried to remove the moisture, it will return to the original physical properties of the polyamide resin, and the molded body will have high heat resistance.
[0075] In-mold molding is carried out, for example, as follows. First, the foamed particles are filled into a mold. Next, steam is supplied into the mold to heat and fuse the foamed particles. After heating, the pressure is released and the molded body is water-cooled until the surface pressure due to the foaming force of the molded body drops to a predetermined pressure (for example, 3.5 to 4.5 MPa (gauge pressure)), after which the mold is opened and the molded body is removed from the mold.
[0076] [Molded body] (Molded body density) From the viewpoint of further improving the light weight, the bulk density of the molded body is 50 to 200 kg / m 3 is preferably 55 to 160 kg / m 3 More preferably, it is 60 to 150 kg / m 3 The density of the molded body is calculated by dividing the mass of the molded body by the external dimensions, and expressed in units of [kg / m 3 The density of the molded article can be adjusted to fall within the above range by using a specific hindered amine compound or thioether compound as described above.
[0077] (Yellow Index YI) From the viewpoint of obtaining a molded product with excellent whiteness, the YI of the molded product is preferably 5 or less. The method for measuring the YI of the molded product will be described later, but it is the YI of the molded product that does not contain a colorant. The YI of the molded product can be easily adjusted to the above range by using a specific hindered amine compound or thioether compound as described above. From the viewpoint of lowering the YI of the molded product, it is preferable not to add a colorant in the method for producing the expanded polyamide resin particles. In addition, although the reason is unclear, when copper iodide is used, the molded product tends to yellow and the YI of the molded product tends to be high. From the above viewpoint, it is preferable not to use copper iodide.
[0078] (Yellow Index YI after heating) From the viewpoint of more adequately preventing discoloration over time in a high-temperature environment, the YI of the molded product after heating at a temperature of 160° C. for 48 hours is preferably 60 or less, more preferably 58 or less, and even more preferably 56 or less. The YI of the molded product after heating can be easily adjusted to the above range by using a specific hindered amine compound or thioether compound as described above.
[0079] (Shrinkage rate after heating) From the viewpoint of more sufficiently preventing shrinkage in a high-temperature environment, the shrinkage rate after heating for 10 days at a temperature of 160° C. is preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less. The shrinkage rate of the molded product after heating can be adjusted to the above range by using a specific hindered amine compound or thioether compound as described above. EXAMPLES
[0080] Next, the present invention will be described in more detail with reference to examples. However, the present invention is not limited to these examples, and various modifications are possible without departing from the gist of the present invention.
[0081] [Example 1] [Production of resin particles] 100 parts by mass of polyamide resin, 0.5 parts by mass of compound (a), and 0.3 parts by mass of a bubble nucleating agent (specifically, talc) were fed to an extruder, and melt-kneaded under conditions where the resin temperature reached 270° C. to obtain a melt-kneaded product. The polyamide resin used was "UBE Nylon 6434B" manufactured by Ube Industries, Ltd., the compound (a) used was the hindered amine compound (a2) poly[6-(1,1,3,3-tetramethylbutyl)imino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidyl)imino]hexamethylene[(2,2,6,6-tetramethyl-4-piperidyl)imino] ("Sabostab UV94" manufactured by SABO) (hereinafter referred to as "compound (a2-1)"), as appropriate, and the bubble nucleating agent used was "Talcan Powder PK-S" manufactured by Hayashi Kasei Co., Ltd. The melt-kneaded product was extruded as a strand with a circular cross section from the small hole of the die attached to the tip of the extruder, and the extruded strand was cooled with water, then cut into pieces with an average mass of 2 mg each using a pelletizer, and dried to obtain pellet-shaped resin particles. The melting point of the resin particles was 186°C. The polyamide resin "6434B" is a polyamide 6 / 66 / 12 copolymer (nylon 6 / 66 / 12), with a melting point (Tm) of 188°C and a density of 1.14g / cm 3 , flexural modulus: 1070 MPa, product name: UBE Nylon 6434B. The melting point of the base resin was 188°C.
[0082] [Production of foamed beads] In a 5-liter autoclave equipped with a stirrer, 500 g of resin particles and 3.5 liters of water as a dispersion medium were charged, and further, 0.3 parts by mass of kaolin as a dispersant and 0.004 parts by mass of sodium alkylbenzene sulfonate as a surfactant were added to 100 parts by mass of resin particles. While stirring the contents in the autoclave, the temperature was raised from room temperature (specifically, 23°C) to the impregnation temperature (131.5°C), and carbon dioxide as a foaming agent was pressed into the autoclave until the pressure in the autoclave reached the impregnation pressure (4.0 MPa (G)). At this time, the temperature rise time from room temperature (23°C) to the impregnation temperature (131.5°C) was 40 minutes. Next, the temperature was held at 131°C and 4.0 MPa (G) for 15 minutes. Thereafter, the resin particles impregnated with the blowing agent were released together with the dispersion medium under atmospheric pressure (0.1 MPa) to expand the resin particles, thereby obtaining expanded particles. The expansion temperature (temperature of the dispersion liquid immediately before expansion) was 131.5°C. The expanded particles were then cured in an oven at 60°C for 24 hours, and then slowly cooled. The expanded particles thus obtained were used for the evaluations described below and for the production of molded bodies.
[0083] [Production of Molded Products] Next, a molded product was produced using the expanded beads. Specifically, after clamping the mold, the obtained expanded mixed resin beads were filled into a flat mold measuring 200 mm in length, 65 mm in width, and 40 mm in thickness, and molding was performed in the mold by steam heating to obtain a plate-shaped expanded molded product.
[0084] The heating method was as follows: with the drain valves on both sides of the mold open, steam was supplied for 5 seconds to perform preheating (exhaust process), then steam was supplied from the moving mold with the drain valve on the fixed side open, and then steam was supplied from the fixed mold with the drain valve on the moving side open, after which the exhaust valve was closed and heating was performed up to a molding heating steam pressure of 0.12 MPa (molding pressure = molding steam pressure). After heating, the pressure was released and the molded body was cooled with water until the surface pressure due to the foaming force of the molded body dropped to 0.02 MPa (gauge pressure), after which the mold was opened and the molded body was removed from the mold. It was then left to stand in an oven at 80°C, and after 24 hours it was taken out to obtain a molded body.
[0085] <Evaluation of Base Resin and Resin Particles> The MFR of the base resin and resin particles was measured at a test temperature of 230°C and a load of 2.16 kg in accordance with JIS K7210-2:2014. The test pieces used to measure the MFR were placed in an oven heated to 80°C and dried for 4 hours. The results are shown in the table.
[0086] <Evaluation of expanded particles> The expanded beads were evaluated as follows, and the results are shown in the table below. (Apparent density) First, a 500 cm sample was left for 2 days under the conditions of 50% relative humidity, 23°C, and 1 atm. 3 The mass W1 of the expanded beads was measured. Next, a measuring cylinder containing water at a temperature of 23°C was prepared, and the expanded beads whose mass had been measured were submerged in the measuring cylinder using a wire net. Taking into account the volume of the wire net, the volume V1 of the expanded beads read from the rise in the water level [unit: cm 3 ] is measured, and the mass W1 [g] of the foamed particles is divided by the volume V1 (W1 / V1), and the unit is [kg / m 3 The apparent density of the expanded beads was calculated by converting the density into the mass ratio (μm).
[0087] (MFR) The MFR of the expanded beads was measured at a test temperature of 230°C and a load of 2.16 kg in accordance with JIS K7210-2:2014. The test pieces used to measure the MFR were dried at 80°C for 4 hours.
[0088] (Percentage reduction in apparent density) The reduction ratio Ds / De was calculated by dividing the apparent density Ds of the expanded beads not containing compound (a) and compound (b) (specifically, the expanded beads of Comparative Example 1) by the apparent density De of the expanded beads of this example.
[0089] <Evaluation of Molded Products> The expanded beads were evaluated as follows, and the results are shown in the table below. (Molded body density) The mass of the molded body is divided by the external dimensions and expressed in units of [kg / m 3 The density of the green body was calculated by converting the density of the green body into the mass per unit area (molecular weight).
[0090] (Yellow Index YI) A test piece cut from the molded product, measuring 50 x 50 x 25 mm in length x width x thickness, was left to stand for 48 hours in a convection oven set to 160°C, after which the test piece was taken out and the YI of the top surface of the test piece was measured using a spectrophotometer (Konica Minolta CM-5) by the reflection method based on ASTM D1925. Measurements were performed on 10 randomly selected points, and the arithmetic average value was used.
[0091] (Heat resistance) After molding, the molded body was dried in a dryer at 60°C for 24 hours to remove moisture. Next, test pieces were prepared and a heating test was conducted in accordance with JIS K6767:1999 Dimensional Stability Evaluation Method B, and the dimensional shrinkage rate (%) was evaluated. The temperature conditions were 160°C and 10 days. As an evaluation standard, the smaller the dimensional shrinkage rate, the more excellent the heat resistance of the foamed molded body was judged to be. Specifically, a dimensional shrinkage rate of 4% or less was evaluated as "good", and a dimensional shrinkage rate of more than 4% was evaluated as "poor".
[0092] (Evaluation of moldability) The moldability (evaluation of moldable pressure) was evaluated by molding the expanded beads in a mold while changing the molding pressure, and evaluating the moldable range. First, the molding pressure was changed by 0.02 MPa between 0.1 and 0.18 [MPa (G): gauge pressure], and molding was performed in a mold at a total of five molding pressures. Next, the molded bodies produced at each molding pressure were evaluated for recovery, appearance, and fusion property by the following methods. Based on the results, the moldable pressure range of the expanded beads was evaluated according to the following criteria. A: There were three or more molding pressures that could produce acceptable products. B: There were two molding pressures at which a qualified product could be molded. C: There was one molding pressure that could produce an acceptable product. D: It was not possible to produce a satisfactory product at any molding pressure.
[0093] (Recoverability) After leaving the molded body for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, the thickness of the central part of the main surface of the flat-shaped molded body (i.e. the surface with the widest area) and the thickness of the four corners of the main surface were each measured. If the ratio of the thickness of the central part to the thickest part of the four corners was 90% or more, it was evaluated as "A (pass)", if it was 80% or more but less than 90%, it was evaluated as "B (fail)", and if it was less than 80%, it was evaluated as "C (fail)".
[0094] (exterior) ·Central part The center of the surface of the flat plate-shaped molded article (specifically, the center of each surface of the molded article) was visually inspected, and the appearance was evaluated according to the following criteria. A (pass): The center of the surface was beautiful and had excellent appearance. B (failed): Voids (specifically, gaps between foam particles) were found in the center of the surface, and the appearance was poor. C (fail): Voids (specifically, gaps between foam particles) were clearly observed in the center of the surface, and the appearance was poor. Corners The corners of the surface of the flat molded product (within a radius of 10 mm from the corner of the molded product) were visually inspected and the appearance was evaluated according to the following criteria. A (Pass): The corners of the surface were beautiful and had an excellent appearance. B (failed): Voids (specifically, gaps between foam particles) were found in the corners of the surface, and the appearance was poor. C (fail): Voids (specifically, gaps between foam particles) were clearly observed at the corners of the surface, and the appearance was poor.
[0095] (Fusing ability) The fusion rate was measured to evaluate the fusion properties of the molded body. A fusion rate of 90% or more was rated as "A (pass)", and a fusion rate of less than 90% was rated as "C (fail)". The fusion rate of the molded body was measured by the following method. A cut was made with a cutter knife on one of the main surfaces of a flat-shaped molded body at a position that divided the vertical length of the molded body into two equal parts in the thickness direction to a depth of about 10 mm, and the molded body was folded and broken from the cut. The ratio (m / n×100[%]) of the number of foamed beads present on the fracture surface that had undergone material destruction to the number n of all foamed beads present on the fracture surface was calculated. If the molded body could not be broken even by folding it, the fusion rate was taken as 100%. The above measurement was carried out five times using different test pieces, and the material destruction rate for each was calculated, and the arithmetic average of these was taken as the fusion rate.
[0096] [Example 2] The procedure was the same as in Example 1, except that compound (a2-1) was replaced with a thioether compound, tetrakis[3-(dodecylthio)propionic acid]methanetetrayltetrakismethylene ("ADK STAB AO-412S" manufactured by ADEKA CORPORATION) (hereinafter referred to as "compound (a1)" as appropriate).
[0097] [Example 3] The procedure was the same as in Example 1, except that compound (a2-1) was replaced with a hindered amine compound, a polycondensate of dibutylamine, 1,3,5-triazine, N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl-1,6-hexamethylenediamine, and N-(2,2,6,6-tetramethyl-4-piperidyl)butylamine ("Chimassorb 2020" manufactured by BASF Japan Ltd.) (hereinafter referred to as "compound (a2-2)" as appropriate).
[0098] [Example 4] The procedure was the same as in Example 1, except that during melt kneading, 0.2 parts by mass of N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide] ("Irganox1098" manufactured by BASF Japan Ltd.), which is a hindered phenol compound (b1), and 0.2 parts by mass of tris(2,4-di-t-butylphenyl)phosphite ("Irgafos168" manufactured by BASF Japan Ltd.), which is an organophosphorus compound (b2), were further supplied to the extruder.
[0099] [Example 5] The procedure was the same as in Example 2, except that during melt-kneading, 0.2 parts by mass of N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide] ("Irganox1098" manufactured by BASF Japan Ltd.), which is a hindered phenol compound (b1), and 0.2 parts by mass of tris(2,4-di-t-butylphenyl)phosphite ("Irgafos168" manufactured by BASF Japan Ltd.), which is an organophosphorus compound (b2), were further supplied to the extruder.
[0100] [Example 6] The procedure was the same as in Example 3, except that during melt-kneading, 0.2 parts by mass of N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide] ("Irganox1098" manufactured by BASF Japan Ltd.), which is a hindered phenol compound (b1), and 0.2 parts by mass of tris(2,4-di-t-butylphenyl)phosphite ("Irgafos168" manufactured by BASF Japan Ltd.), which is an organic phosphorus compound (b2), were further supplied to the extruder.
[0101] [Example 7] The procedure was the same as in Example 1, except that the amount of compound (a2-1) added as compound (a) was changed to 0.2 parts by mass and fed to the extruder.
[0102] [Example 8] The procedure was the same as in Example 1, except that the amount of compound (a2-1) added as compound (a) was changed to 1.0 part by mass and fed to the extruder.
[0103] [Example 9] The procedure was the same as in Example 1, except that during melt kneading, 0.05 parts by mass of N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide] ("Irganox1098" manufactured by BASF Japan Ltd.), which is a hindered phenol compound (b1), and 0.05 parts by mass of tris(2,4-di-t-butylphenyl)phosphite ("Irgafos168" manufactured by BASF Japan Ltd.), which is an organophosphorus compound (b2), were further supplied to the extruder.
[0104] [Example 10] The procedure was the same as in Example 1, except that during melt kneading, 0.5 parts by mass of N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide] ("Irganox1098" manufactured by BASF Japan Ltd.), which is a hindered phenol compound (b1), and 0.5 parts by mass of tris(2,4-di-t-butylphenyl)phosphite ("Irgafos168" manufactured by BASF Japan Ltd.), which is an organophosphorus compound (b2), were further supplied to the extruder.
[0105] [Comparative Example 1] The procedure was the same as in Example 1, except that compound (a) was not fed to the extruder during melt-kneading.
[0106] [Comparative Example 2] During melt kneading, compound (a) was not supplied to the extruder, and instead, 0.2 parts by mass of N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4 hydroxyphenylpropionamide] ("Irganox1098" manufactured by BASF Japan Ltd.), which is a hindered phenol compound (b1), and 0.2 parts by mass of tris(2,4-di-t-butylphenyl)phosphite ("Irgafos168" manufactured by BASF Japan Ltd.), which is an organic phosphorus compound (b2), were supplied to the extruder, similarly to Example 1.
[0107] [Comparative Example 3] During melt kneading, the same procedure as in Example 1 was repeated except that, as compound (a), instead of compound (a2-1), bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate ("Tinuvin770" manufactured by BASF Japan Ltd.), a hindered amine compound, was used, and as compound (b), 0.2 parts by mass of N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide] ("Irganox1098" manufactured by BASF Japan Ltd.), a hindered phenol compound (b1), and 0.2 parts by mass of tris(2,4-di-t-butylphenyl)phosphite ("Irgafos168" manufactured by BASF Japan Ltd.), an organic phosphorus compound (b2), were supplied to the extruder.
[0108] [Comparative Example 4] The procedure was the same as in Example 1, except that during melt-kneading, 0.05 part by mass of copper iodide and 0.2 part by mass of potassium iodide were fed to the extruder as compound (a) instead of 0.5 part by mass of compound (a2-1).
[0109] [Comparative Example 5] The procedure was the same as in Example 1, except that, during melt-kneading, a hindered amine compound, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate ("Tinuvin 770" manufactured by BASF Japan Ltd.), was used as compound (a) instead of compound (a2-1).
[0110] [Comparative Example 6] The procedure was the same as in Example 1, except that 2 parts by mass of the compound (a2-1) was used as the compound (a) during melt-kneading.
[0111] [Table 1]
[0112] [Table 2]
[0113] [Table 3]
[0114] [Table 4]
[0115] [Table 5]
[0116] [Table 6]
[0117] [Table 7]
[0118] As can be seen from Tables 1 to 7, in the examples, the shrinkage rate of the molded article after exposure to a high-temperature environment is low, and the heat resistance is excellent. In addition, the pressure range in which molded articles with good fusion properties, recovery properties, and appearance can be molded is wide, and the moldability is excellent. This is because in the examples, a thioether-based compound and a hindered amine-based compound having a molecular weight of 500 or more are blended as compound (a) in a predetermined ratio with respect to the base resin.
[0119] Furthermore, as can be seen by comparing Example 1 with Example 4, Example 2 with Example 5, and Example 3 with Example 6, respectively, the moldability is further improved by using a specific compound (a) (specifically, a thioether-based compound, a hindered amine-based compound having a molecular weight of 500 or more) in combination with a specific compound (b) (specifically, a hindered phenol-based compound, an organic phosphorus-based compound).
[0120] In Comparative Example 1, since the compound (a) was not added, the yellow index after heating and the shrinkage rate after exposure to a high temperature environment were high, and the heat resistance was poor. In addition, the obtained molded product had poor surface properties at the corners. In Comparative Example 2, although the compound (b) capable of exerting an antioxidant effect is added, the compound (a) is not added as in Comparative Example 1, and therefore the heat resistance is poor.
[0121] In Comparative Examples 3 and 5, a hindered amine compound having a low molecular weight is used as the compound (a), which results in poor heat resistance. In Comparative Example 4, copper iodide and potassium iodide were used, and a thioether compound and a hindered amine compound having a molecular weight of 500 or more were not used, resulting in insufficient moldability. In addition, yellowing easily occurs, and the YI before and after heating are high. In Comparative Example 6, the hindered amine compound was too much, so the hindered amine compound acted as a plasticizer, leading to poor recovery and insufficient moldability. In addition, the molded product had poor recovery, so it contracted significantly after heating and had insufficient heat resistance.
[0122] In this way, when carrying out the preparation step and the expansion step to produce expanded polyamide resin beads, compound (a) containing a thioether compound and / or a hindered amine compound having a molecular weight of 500 or more is used, and the total amount of the thioether compound and the hindered amine compound having a molecular weight of 500 or more added per 100 parts by mass of the base resin is set to 0.05 parts by mass or more and 1 part by mass or less, thereby making it possible to produce expanded beads having excellent heat resistance and moldability. With the expanded beads thus obtained, a molded article having good fusibility, recovery property, and appearance can be obtained over a wide range of molding pressures, and the molded article also has excellent heat resistance.
Claims
1. A method for producing expanded polyamide resin beads, comprising the steps of: preparing polyamide-based resin particles containing a base resin mainly composed of a polyamide-based resin and a compound (a) consisting of a thioether-based compound (a1) and / or a hindered amine-based compound (a2) having a molecular weight of 500 or more; and a step of expanding the polyamide-based resin particles using a physical foaming agent to obtain expanded polyamide-based resin particles, The method for producing expanded polyamide resin particles, wherein the compound (a) is added in an amount of 0.05 parts by mass or more and 1.5 parts by mass or less based on 100 parts by mass of the base resin.
2. The method for producing expanded polyamide resin beads according to claim 1, wherein the polyamide resin particles further contain a compound (b) consisting of a hindered phenol compound (b1) and / or an organic phosphorus compound (b2).
3. 3. The method for producing expanded polyamide resin beads according to claim 1 or 2, wherein the compound (a) comprises at least one compound selected from the group consisting of hindered amine compounds represented by the following formula (1) and having a molecular weight of 500 or more, hindered amine compounds represented by the following formula (2) and thioether compounds represented by the following formula (3): 【Chemistry 1】 (In the above formula (1), n represents 2 to 10 repeating units.) 【Chemistry 2】 (In the above formula (2), n represents 1 to 10 repeating units.) 【Chemistry 3】 (Note that in the formula (3), each R independently represents an alkyl group having 1 to 20 carbon atoms.)
4. 3. The method for producing expanded polyamide resin beads according to claim 1, wherein the compound (a) is added in an amount of 0.3 part by mass or more and 1 part by mass or less based on 100 parts by mass of the base resin.
5. A method for producing a polyamide resin foamed article, comprising molding the expanded polyamide resin beads produced by the method according to claim 1 or 2 in a mold.
Citation Information
Patent Citations
Polyamide resin prefoamed particle, polyamide resin foamed molded article, and method for manufacturing polyamide resin foamed molded article
WO2020196893A1